2002
DOI: 10.1128/aem.68.5.2584-2588.2002
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of 2,7-Dichloro- and 1,2,3,4-Tetrachlorodibenzo- p -Dioxin by Sphingomonas wittichii RW1

Abstract: Aerobic biotransformation of the diaryl ethers 2,7-dichlorodibenzo-p-dioxin and 1,2,3,4-tetrachlorodibenzop-dioxin by the dibenzo-p-dioxin-utilizing strain Sphingomonas wittichii RW1, producing corresponding metabolites, was demonstrated for the first time. Our strain transformed 2,7-dichlorodibenzo-p-dioxin, yielding 4-chlorocatechol, and 1,2,3,4-tetrachlorodibenzo-p-dioxin, producing 3,4,5,6-tetrachlorocatechol and 2-methoxy-3,4,5,6-tetrachlorophenol; all of these compounds were unequivocally identified by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 22 publications
2
47
0
1
Order By: Relevance
“…Alternatively, it is possible that the physiological substrate of DxnB2 is substituted 8-OH HODPA. For example, it has been reported that S. wittichii RW1 metabolizes 4-chlorodibenzofuran and 2,7-dichlorodibenzo-p-dioxin to form 9-Cl-, 10-Cl-, or 11-Cl-substituted 8-OH HOPDA (1,17). Consistent with this possibility, DxnB2 possessed higher specificity for 9-Cl and 10-Cl HOPDAs than for unchlorinated HOPDA (Table 1).…”
Section: (4) Dsupporting
confidence: 72%
“…Alternatively, it is possible that the physiological substrate of DxnB2 is substituted 8-OH HODPA. For example, it has been reported that S. wittichii RW1 metabolizes 4-chlorodibenzofuran and 2,7-dichlorodibenzo-p-dioxin to form 9-Cl-, 10-Cl-, or 11-Cl-substituted 8-OH HOPDA (1,17). Consistent with this possibility, DxnB2 possessed higher specificity for 9-Cl and 10-Cl HOPDAs than for unchlorinated HOPDA (Table 1).…”
Section: (4) Dsupporting
confidence: 72%
“…In the case of 2,4,8-TrCDF, 6,8-dichloro-2-methyl-4H-chromen-4-one was produced as the metabolite. Hong et al 89) reported that Sphingomonas wittichii strain RW1 transformed 2,7-DCDD and 1,2,3,4-TCDD to 4-chlorocatechol and 3,4,5,6-tetrachlorocatechol, respectively. A second metabolite, 2-methoxy-3,4,5,6-tetrachlorophenol, was produced from the original degradation product, 3,4,5,6-tetrachlorocatechol, by methylation of one of the two hydroxy substituents.…”
Section: Biodegradation Of Chlorinated Congenersmentioning
confidence: 99%
“…Consequently, numerous studies have been carried out to elucidate the aerobic (7,9,19) bacterial degradation of PCDD/Fs, compounds produced by incineration processes and as unwanted by-products of the synthesis of pesticides and herbicides (4,17). However, naturally occurring microorganisms have evolved to degrade and mineralize many, but by no means all, of these compounds.…”
mentioning
confidence: 99%
“…In addition to genera such as Terrabacter (6,14) and Pseudomonas (6), several strains belonging to the genus Sphingomonas were reported to use diaryl ethers such as dibenzofuran and dibenzo-p-dioxin as the sole source of carbon and energy (3). Some of these isolates are examples for effective biocatalysts that can even catabolize some di-, tri-, and tetrachlorinated dibenzo-p-dioxins and dibenzofurans (6,7,9,19). However, the aerobic catabolism of important environmental pollutants such as 1,2,3,7,8-penta-or 1,2,3,4,7,8-hexachlorodibenzo-p-dioxin, giving rise to the formation of corresponding metabolites, has not been demonstrated previously.…”
mentioning
confidence: 99%